Optimization Strategy for The HEBITREN Program and Halal Value Chain in Developing The Sharia Economy - Br. Lumban Tobing, Fanny Asyifa; Harahap, Isnaini; Daulay, Aqwa Naser (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
There is a problem that often arises: Islamic boarding schools are still lacking in terms of income to manage and drive the Islamic boarding school economy. Islamic boarding schools are often only fixated on student dues as a funding source for various purposes, including economic development and infrastructure. Therefore, the researcher intends to analyze one way to encourage the economic independence of Islamic boarding schools through the optimization of the Hebitren program and the potential of the halal value chain for the development of the Islamic economy in Islamic boarding schools. The method raised in this study is a qualitative method where the researcher goes directly to the location of the case study to obtain information which then the results of the study are processed and analyzed using the SOAR framework and the IFAS / IFES matrix and then described descriptively. The results of the study show that the most appropriate strategy to optimize the economic independence of Islamic boarding schools through the Hebitren program and the potential of the halal value chain is the SA strategy, namely developing quality human resources and playing an active role in developing business models based on Islamic values, streamlining the concept of halal value chain, managing Islamic boarding school assets, entrepreneurship training, and strengthening business networks